TRANSPARENCY AND PUBLIC ACCOUNTABILITY THROUGH PUBLIC SECTOR ACCOUNTING: THE USE OF ‘VALUE FOR MONEY’ CONCEPT IN INDONESIA - Trimarstuti, Jeki (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
Two of the most fundamentalist concepts for reshaping the regional public finance are the transparency process and the public accountability through the public sector accounting. To support the realization of both of these ideas, there is a concept that has been discussed in the term of local public accounting system recently, which is called ?Value for Money?. By using Content Analysis method, the aim of this study is to find out more about the issue problem and the use of ?Value For Money? to analyze the transparency and public accountability problem in Indonesia.